Conceptualizing ‘Children’ across Age Groups in Lithuania: A Preliminary Account Using Free List Tasks - Charenkova, Jūratė (Vilnius University Open Series, 2025)
A variety of economic, personal and social reasons may have influenced Lithuanians changing attitudes toward having children, which has been causing a significant fertility decline since the early 1990s. The conceptions one has about children may affect the decision to have or not to have children. By applying a bottom-up anthropological research design, this paper aims to examine the relationship between social contexts and cultural norms as they influence the way people of different generations conceptualize children. The results of the study reveal that the conceptions one has about children are subject to change. This change can be influenced either by real life experiences of raising one’s own children, by observing others raising their children, or by other socially, culturally or psychologically motivated reasons. Hence, the shift in the perception of ‘children’ over the life cycle is the focus of this paper.